1998
DOI: 10.1002/(sici)1521-3951(199812)210:2<437::aid-pssb437>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Doping of Homoepitaxial GaN Layers

Abstract: Gallium nitride doped with oxygen (unintentionally), silicon and magnesium was grown by metalorganic chemical vapor deposition on the conductive single crystals of GaN grown at high hydrostatic pressure. The layers were examined using X-ray diffraction, photoluminescence and far-infrared reflectivity. It was found that the incorporation of silicon depends on the side used for deposition. For the two Si-doped layers grown in the same run, the one grown on the (00.1) side (gallium-terminated) had always smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 6 publications
3
31
0
Order By: Relevance
“…Smaller FWHM values of O 0 X A and Si 0 X A (0.45 meV for O 0 X A and 0.29 meV for Si 0 X A ) are consistent with a lower incorporation of impurities in the gallium-face epilayer. The intense broad band observed at $3.48 eV has previously been assigned to a high concentration of free electrons [25]. Preliminary studies performed on a selected thicker region of the layer showed no evidence of this broad band.…”
Section: Resultsmentioning
confidence: 79%
“…Smaller FWHM values of O 0 X A and Si 0 X A (0.45 meV for O 0 X A and 0.29 meV for Si 0 X A ) are consistent with a lower incorporation of impurities in the gallium-face epilayer. The intense broad band observed at $3.48 eV has previously been assigned to a high concentration of free electrons [25]. Preliminary studies performed on a selected thicker region of the layer showed no evidence of this broad band.…”
Section: Resultsmentioning
confidence: 79%
“…This intense luminescence peak indicates a good luminescence property of the crystals grown at these rates, compared with the relatively weak luminescence peak of the bar crystals grown by the previously reported CRN method [11]. The upward energy shift of the band-edgerelated luminescence peak ($3.47 eV) from the reported value ($3.42 eV) is probably attributed to the high concentration of oxygen [20,21], described below. On the other hand, the crystals grown at the rates of 2 and 15 mmol/min show the weak and broad luminescence peaks at $3.4 and $1.8 eV (Fig.…”
Section: Growth Of Gan Crystalsmentioning
confidence: 48%
“…It has been reported that the nominally undoped GaN epitaxial film grown in MOCVD system is normally n-type, which is mainly attributed to the existence of oxygen impurity and vacancy defects. [16][17][18][19][20] As InGaN LD is a kind of device with P-I-N junction, the n-type background concentration of unintentionally doped GaN interlayer may changes the depletion region near the interface of p-/n-doped layers. As the unintentionally doped GaN interlayer is normally n-type while Al 0.2 Ga 0.8 N EBL is p-type, a depletion region will exist on both sides of u-GaN/Al 0.2 Ga 0.8 N interface.…”
Section: B Effect Of Background Concentration Of Unintentionally Dopmentioning
confidence: 99%